Social Workers' Attitudes Toward Medical Assistance in Dying for Persons With Dementia: Findings From a Survey Conducted in Quebec, Canada. Issue 3 (3rd July 2022) - Bravo, Gina; Delli-Colli, Nathalie; Dumont, Isabelle; Bouthillier, Marie-Eve; Rochette, Marianne; Trottier, Lise
Abstract: Canada has legalized medical assistance in dying (MAID) for mentally competent persons who satisfy the legal requirements. Debate is ongoing as to whether MAID should be accessible to no-longer-competent persons through an advance request. We conducted an anonymous vignette-based survey among 367 social workers from Quebec to (1) elicit their attitudes toward MAID in the context of dementia; (2) assess their underlying values and beliefs; and (3) compare their attitudes to those of nurses ( n = 291) and physicians ( n = 136). Acceptability of MAID among social workers ranges from 42% in the case where the person depicted in the vignette was still competent to request MAID herself, to 92% in that where she was incompetent, had requested MAID in writing before losing capacity, showed signs of severe distress, and was close to death. Acceptability tends to be higher among social workers than among nurses and physicians. Forty-one per cent of social workers dread the prospect of participating in the MAID process for a person lacking decisional capacity. Nonetheless, 83% would agree to be involved. Should MAID become accessible to persons lacking decisional capacity, social workers willing to be involved will need to be educated and trained in participating in this emotionally-charged process.